1981
DOI: 10.1002/jlac.198119810406
|View full text |Cite
|
Sign up to set email alerts
|

Die relative Konfiguration der Chebulsäure

Abstract: Entgegen früheren Aussagen besitzt die Chebulsäure 2 die relative Konfiguration 2R,3S,4R oder 2S,3R,4S. Dies wurde durch synthetische und NMR‐spektroskopisch Beweise sowie durch eine Röntgenstrukturanalyse festgestellt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The isolated materials actually consist of two epimers, ( S , S , S )‐ 1 and (3 S ,4 S ,9 R )‐ 1 (Figure 1). The relative trans ‐configuration at C3 and C4 was already earlier established by X‐ray structure of the triethylester of chebulic acid [9] …”
Section: Introductionmentioning
confidence: 62%
“…The isolated materials actually consist of two epimers, ( S , S , S )‐ 1 and (3 S ,4 S ,9 R )‐ 1 (Figure 1). The relative trans ‐configuration at C3 and C4 was already earlier established by X‐ray structure of the triethylester of chebulic acid [9] …”
Section: Introductionmentioning
confidence: 62%
“…The small coupling constants (1.4 Hz) between H-3 and H-4 confirmed their trans-diequatorial relative configuration. 6,17 Euphorhirtins C−E (3−5) had the same molecular formula, C 18 H 18 O 11 , as determined by their positive-ion HRESIMS and 13 C NMR data. Analysis of their 1 H and 13 C NMR data (Table 1) revealed that the structures of 3−5 were similar to 15, the difference being the presence of only two ethoxy groups in 3− 5.…”
mentioning
confidence: 85%
“…Thus, the 2D structure of euphorhirtin A (1) was assigned and confirmed by analysis of its HMBC spectrum (Figure 1). The small 3 J 3,4 value of 2.0 Hz, 6,17 along with the NOESY correlation of H-3/H-4 indicated that H-3 and H-4 adopted a trans-diequatorial relative configuration with both hydrogens in an equatorial orientation. However, the configuration of the C-11−C-12 double bond could not be determined from the available data.…”
mentioning
confidence: 96%
“…A skeleton of this type is reported in the literature for chebulic acid. 35,36 However, chebulic acid 2S, 3S, 4S 37 is the hydrolysis product of chebulinic and chebulagic acid 36 and is not a naturally occurring compound.…”
Section: Structure Elucidation Of B3ea-6mentioning
confidence: 98%